Penentuan Komoditas Perkebunan Unggulan di Provinsi Jawa Barat - Bayu Kharisma; Yudha Hadian Nur (MediaTrend, 2019)
This paper aims to analyze superior plantation commodities in West Java Province, identify plantation superior commodities according to current potential aspects and future prospects and develop strategies for developing plantation superior commodities as a basis for reference to the direction of plantation development policies in West Java Province. The methodology used in this study is the Exponential Comparison Method (MPE) and the Borda Method to determine the potential of superior plantation commodity products. The next stage is to do projections (forecasting) by mapping the various commodities based on the results of the assessment of the current prospect and potential factors. Finally, formulate a variety of alternative strategies based on current potential and future prospects. Coffee plants are the main superior commodity belonging to the strategic commodity group of plantations in West Java. Furthermore, sugar palm plants are designated as the main superior prospective commodity. Finally, the indigofera plant is the main specific superior commodity determined based on the results of the Exponential Comparison Method (MPE). The mapping results and projections for strategic plantation commodities in West Java Province that have future prospects based on current potentials are coffee and deep coconut plants. Prospective commodity plantations in West Java Province that have future prospects based on current potential, namely sugar palm, pepper, patchouli and nutmeg, while local specific superior commodities of plantations in West Java have good prospects and high potential, namely indigofera, lemongrass fragrant, and mustache cat. The results of ranking and mapping or the position of strategic plantation commodities can be determined by several strategies which include short-term, medium-term and long-term development strategies.